Student`s conceptions on digital information and communication technologies for legal activities (Research, Society and Development, 2019)
This study aims to verify, from the perspective of the first and final students of the tenth period of the Law course, what knowledge and skills they have on the TDIC (Digital Information and Communication Technology) used by Law professionals in the exercise of legal activities. To answer the proposed question a descriptive, analytical and quantitative research was carried out. Questionnaires were applied to incoming and completing students of a law course of a private institution in the city of Belo Horizonte - MG. The sample consisted of 192 respondents. Women are majority in the course researched; 67.9% of participants are between 18 and 24 years old; 23.5% of the graduating students and 8.9% of the incoming students take an extracurricular internship in the area. Regarding the knowledge in the TDIC used in the practical activities of professionals working in the legal area, it was verified that among the students who study and stage, 63.8% are familiar with the programs. 18.2% described having good mastery over the Electronic Judicial Process.